Taxonomic studies on the genus Delphinium (Ranunculaceae) from China (XVIII): Towards clarification of the confusion of D. iliense with special reference to observations on living plants in the Ili region in northwestern Xinjiang - Li, Hui-Min; Yuan, Qiong; Yang, Qin-Er (Phytotaxa, 2019)
Based on observations on living plants in the field, together with examination of herbarium specimens (including type material), we demonstrate that Delphinium iliense (Ranunculaceae) is highly variable in the indumentum of peduncles, pedicels, bracteoles, sepals and carpels and also in the shape of bracteoles and their position on pedicels. We therefore redefine this species and, in addition to accepting some previous synonyms in this species, such as D. longiciliatum and D. turkestanicum, we further reduce D. iliense var. angustatum and D. naviculare to its synonymy. We also propose lectotypification for D. iliense var. angustatum and D. turkestanicum.